2016
DOI: 10.1007/s11134-016-9481-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimal control of queueing systems with non-collaborating servers

Abstract: Throughput values for systems with N = 2 and non-homogeneous tasks 4 Throughput values for systems with N = 3 and non-homogeneous tasks 5 Throughput values for systems with N = 4 and non-homogeneous tasks 6 Throughput values for systems with N = 5 and non-homogeneous tasks 7 Throughput values for systems with N = 2 and homogeneous tasks . 8 Throughput values for systems with N = 3 and homogeneous tasks . 9 Throughput values for systems with N = 4 and homogeneous tasks . 10 Throughput values for systems with N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…For systems with N tasks and N workers without any reassignment costs, Işık et al. (2016) characterized a special case in which each worker is the most skilled worker at a different task and showed that in this case, a dedicated worker assignment policy is optimal. The following proposition generalizes that result for systems with positive worker reassignment costs.…”
Section: Structural Results: When Cross‐training Is Not Beneficialmentioning
confidence: 99%
See 3 more Smart Citations
“…For systems with N tasks and N workers without any reassignment costs, Işık et al. (2016) characterized a special case in which each worker is the most skilled worker at a different task and showed that in this case, a dedicated worker assignment policy is optimal. The following proposition generalizes that result for systems with positive worker reassignment costs.…”
Section: Structural Results: When Cross‐training Is Not Beneficialmentioning
confidence: 99%
“…Proposition 4 shows that the optimal policy identified by Işık et al. (2016) for systems with no reassignment costs can perform arbitrarily bad when worker reassignments are costly. We perform a similar numerical comparison between the collaborative and non‐collaborative settings by using the partial results by Andradóttir et al.…”
Section: Two‐station Systems With Homogeneous Tasksmentioning
confidence: 95%
See 2 more Smart Citations
“…Ahn and Lewis (2013) study the dynamic allocation of two flexible servers in a two-station parallel network, along with the dynamic routing decisions, for revenue management purposes. Flexible server allocation is commonly studied in tandem networks (Farrar, 1993;Ahn et al, 1999;Andradóttir et al, 2001;Ahn et al, 2002;Schhiefermayr and Weichbold, 2005;Andradóttir and Ayhan, 2005;Dobson et al, 2012;Işık et al, 2016;Papachristos and Pandelis, 2019;Lim et al, 2020). Among these, some study a clearing tandem network with no external arrivals (Ahn et al, 1999;Schhiefermayr and Weichbold, 2005;Farrar, 1993;Papachristos and Pandelis, 2019;Lim et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%